ANALISIS NERACA AIR DI KECAMATAN SAMBUTAN SAMARINDA - Suratmi . (Universitas 17 Agustus 1945 Samarinda, 2013)
The objective of study was to identify the fluctuation of water balance at Sambutan sub-District of Samarinda. It lasted for about three months, from May until July 2012 in Sambutan Sub District of Samarinda Municipality. Result of the study showed that the fluctuation of water balance at Sambutan-Samarinda have nine months water surplus (223 mm year-1) and three months water deficits (72 mm year-1).